Regulation of Nursing and Midwifery in Nepal - Pokhrel, Tara (Journal of Nursing Education of Nepal, 2011)
Nepal Nursing Council was formed under the Ministry of Health in 2052 BS. It is a legal body mandated and approved by the Government of Nepal for the systematic regulation of the nursing profession in the country. For the purpose of proper operation of the profession, there are 11 board members nominated by Government authority and 4 members elected by the member of Nursing Association. The council has formed a code of conduct to run the profession smoothly so if any practitioner violated the ethical practice (misconduct). The council has right to investigate and if sanctioned for unprofessional conduct, the council can reprimand, admonish, probation, suspend or revoke the license.